The legal basis for the compulsory vaccination of higher education institutions' staff in the COVID-19 pandemic - Khatniuk, Natalia; Pobiyanska, Nelly; Levytska, Anastasia (ScienceRise: Juridical Science, 2022)
The research consists in a theoretical analysis and legislative definition of the concept of mandatory vaccination of employees of higher education institutions and the legal status of dismissed employees who were not vaccinated during the COVID-19 pandemic, regarding the performance of their employment duties under an employment agreement or contract. The authors draw attention to the peculiarities of the legislative regulation of the epidemic and pandemic in Ukraine, as well as the impact of such provisions on the labor relations between employees and employers of individuals and legal entities. The issues of legality and legislative validity of the application of mandatory vaccination for employees of higher education institutions are revealed, as well as the legal consequences of suspension from work of employees who refused to be vaccinated during the COVID-19 pandemic under national legislation, the rules of conduct of the employer in such circumstances and the legal regime of the pandemic as a social phenomenon, determined by the legislator, are analyzed. The legal grounds and ways to protect the labor rights and legitimate interests of employees of higher education institutions are investigated. The list of all categories of employees who are obliged to be vaccinated is revealed. The options for the behavior of the employer and the employee in case of such force majeure are proposed. The legal provisions on the protection of the rights and legitimate interests of employees in the event of a pandemic and the procedure for their dismissal from work in the absence of vaccination are analyzed